ANALISIS PERGESERAN STRUKTUR EKONOMI DAN POTENSI SEKTOR EKONOMI KABUPATEN BADUNG DI ERA PANDEMI COVID-19 - Gede Crisna Wijaya (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The economic potential of a region can be seen especially through leading sectors when facing the current covid19 pandemic so that these leading sectors can be maximized. The purpose of this study is to determine the condition of the shift in the economic structure of Badung Regency, the contribution of the economic sector to the GDP of Badung Regency, and the leading sectors in Badung Regency. The data used in this study uses secondary time series data from Gross Regional Domestic Product which the authors obtained from the Central Statistics Agency of Badung Regency and Bali Province for the period 2015 to 2020. The analysis method in this study uses Klassen Typology analysis, Location Quotioent analysis, Growth Ratio Model analysis, Overlay analysis, and Shift Share analysis. The results of the Klassen Typology analysis show the construction sector; the information and communication sector belongs to the advanced and rapidly growing category. Overlay analysis results show that the construction sector; transportation and warehousing sector; the sector of providing accommodation and food and drink; Information and Communication sector is a very dominant economic sector. The results of the Shift Share analysis show that Badung Regency has not experienced a shift in the economic structure during the COVID-19 pandemic